How learning facilitators teach adults with mild and moderate intellectual disability in learnership programmes at post-school institutions in Cape Town: A descriptive qualitative study - Feinberg, Taryn (Division of Occupational Therapy, 2019)
Introduction: Adults with intellectual disability (ID) have a right to be included in post-school education (PSE) opportunities such as learnership programmes. They face many barriers, however, including the fact that learning facilitators do not know how to include and teach these learners with ID in a PSE context. Problem: No literature or documented evidence has been captured about inclusive educational approaches describing how learning facilitators taught adults with ID in three learnership programmes that can be used to develop training programmes that will equip learning facilitators with the necessary skills for teaching this group of learners. Rationale: Learning facilitators need to be adequately trained, equipped and supported to meet specific learning needs of adults with ID in learnerships. This study will provide a resource of practice-based educational strategies that could serve as the basis for this training. Aim: To describe how learning facilitators in learnership programmes at Organisation X provided teaching to adults with ID. Method: An indepth, moderately structured, open-ended interview method was used to collect data from six participants. Three Universal Design for Learning (UDL) principles and related guidelines were used to inform how the interview questions were structured. Findings: The main theme was “a learnership takes time, patience and many adjustments but it has to be done” that comprised three categories: namely “dealing with intellectual disability”, “streamlining learnership strategies” and “perceiving the 'just right’ learnership”. The sub-categories identified were populated into the UDL Framework. Discussion: Learnership programmes with adults with ID are time consuming and personally demanding for learning facilitators, but adults with ID have a right to access these programmes. Training programmes for learning facilitators need to include aspects of how to deal with learners with ID, what curriculum differentiation strategies need to be streamlined, and how to create the 'just right’ learnership. Conclusions: Learning facilitators believe that learners with ID have the right to access PSE and participate in learnerships. The success of post-school learnerships lies in providing the “just right” curriculum that offers support for both educator and learner.